Money and Banking Statistics in Former Soviet Union (FSU) Economies - Nahr, K. (IMF Working Papers; Working Paper ;, 1992)
This paper addresses the major issues concerning the compilation of money and banking statistics for the fifteen republics of the former Soviet Union (FSU), including (1) the treatment of ruble currency circulation and (2) the classification of claims on FSU financial institutions. The paper proposes the use of a monetary authorities' account to encompass both the domestic and foreign aspects of ruble currency circulation and a classification scheme for monetary accounts that permits the construction of analytically meaningful monetary aggregates. These issues are addressed within an analytical framework that transforms the Gosbank Accounting System into monetary statistics broadly consistent with the Fund's methodology.